ზოდიაქოსთან დაკავშირებული ტერმინოლოგიის ქართულად გადმოცემის თავისებურებები (კლავდიუს პტოლემაიოსის ნაშრომების მიხედვით) - ფოფხაძე გვანცა (ლოგოსი, 2025)
Claudius Ptolemy organized and synthesized prior Greek, Babylonian, and Egyptian concepts into a logical framework, systemizing old astronomical and astrological knowledge. He used mathematical accuracy to develop the geocentric model in Almagest, standardizing ideas such as eccentric orbits and epicycles. He categorized celestial influences in Tetrabiblos and organized astrology using a rational, almost scientific method. This combination is reflected in his nomenclature — astronomical terms became more precise, while astrological language adopted a structured, philosophical tone, reinforcing astrology as a predictive “science” rather than mere superstition. The translation of Claudius Ptolemy’s astronomical and astrological terminology presents significant challenges due to the complexity and precision of his Greek vocabulary. His works, particularly Almagest and Tetrabiblos, integrate mathematical, philosophical, and astrological concepts that lack direct modern equivalents. Key difficulties include the technical nature of his geometric models, the nuanced meaning of astrological terms, and the ambiguity of certain Greek words. Additionally, cultural shifts in scientific discourse require careful balancing between historical accuracy and modern readability. Successful translation needs to maintain Ptolemy’s intellectual structure while providing clarity in present-day language. When translating these terms into Georgian, it would be preferable to: 1) Use the original word instead of the modernized one; 2) Keep the corresponding word in the Georgian language, where tradition is strong; 3) Keep the translation accurate when the author uses synonyms with subtle differences.